Design and Development of a Customer Management System in the Food Industry - Zhekova Mariya; Katrandzhiev Nedyalko; Petkov Mario (BIO Web of Conferences)
The article presents the design and customer management system development process using Python, PostgreSQL, and Tkinter in the food industry. The application aims to provide the ability to perform all CRUD operations related to business processes and make dynamic inquiries related to customer management. It stores information about customers, materials and suppliers, generates reports and provides business process management. The system is designed as a desktop application for small and medium business owners who can make complex management decisions based on the information received. The application is suitable for laboratories, hotels, stores selling food and household goods, various types of orders and services related to food products etc. For its creation, a programming language was used – Python, a relational database – PostgreSQL, for the GUI implementation– Tkinter and for version control – Git and GitHub. In the implementation we have adhered to all good programming practices. The detailed description of the program code aims to demonstrate its efficiency, functionality, simplicity, flexibility and adaptability. Creating the database and the relationships between the objects demonstrate the program integrity, security and normalisation of the data. The application implementation is a step towards the food industry’s digitalisation making it more flexible and adaptable to market changes. The system helps small and medium-sized business owners make important management decisions that determine their success and prosperity. It is suitable for small startup projects in most cases do not have a large budget for purchasing customer management software.